2003
DOI: 10.1177/004051750307300909
|View full text |Cite
|
Sign up to set email alerts
|

Determining Effective Thermal Conductivity of Multilayered Nonwoven Fabrics

Abstract: The average effective thermal conductivity Keff is measured for forty-eight multilayered needle-punched nonwoven samples. Samples are produced using glass and ceramic fibers layered in several different constructions and punched with needles with varying numbers of barbs. The thermal conductivities are determined at steady state, using a Holometrix guard hot plate at an average applied temperature of 455°C. Statistical results show an ability to predict effective thermal conductivity with greater than 88% accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 5 publications
2
38
0
Order By: Relevance
“…As reported by researchers, fibrous thermal insulating nonwovens can be affected by fiber diameter, volume fraction, fiber conductivity, and fiber radiation [9][10][11]. Mohammadi et al indicated that affecting parameters of the thermal insulation model include fabric weight, thickness, porosity, and structure, along with the applied temperature [12]. Based on these, thermal-bonded temperature and time of low-melting point affected the porosity and structure of the resultant composites.…”
Section: Introductionmentioning
confidence: 96%
“…As reported by researchers, fibrous thermal insulating nonwovens can be affected by fiber diameter, volume fraction, fiber conductivity, and fiber radiation [9][10][11]. Mohammadi et al indicated that affecting parameters of the thermal insulation model include fabric weight, thickness, porosity, and structure, along with the applied temperature [12]. Based on these, thermal-bonded temperature and time of low-melting point affected the porosity and structure of the resultant composites.…”
Section: Introductionmentioning
confidence: 96%
“…The exchange of heat follows a distinct phenomena of simultaneous conduction, convection, and radiation. Heat transfer through conduction and radiation has been well understood and documented [1][2][3][4][5][6]. However, convective heat transfer through the fabric is difficult to model as there are no exact solutions for porous material under heat convection as well as the limited research work in this area [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are also analytical studies dealing with the effects of fiber orientation and fiber length on thermal conductivity (see for instance [8,9]). There are also numerous predominantly experimental studies reporting on the thermal insulation properties of different fibrous materials obtained, for instance, by a guarded hot plate apparatus [10,11]. In such studies, performance of the material in blocking conductive and radiative heat transfer is often lumped together in the form of an effective conduction-radiation thermal conductivity [10,11].…”
Section: Introductionmentioning
confidence: 99%